Structural Mechanism of Organic Hydroperoxide Induction of the Transcription Regulator OhrR - Kate J. Newberry (2018)
The Xanthomonas campestris transcription regulator OhrR contains a reactive cysteine residue (C22) that upon oxidation by organic hydroperoxides (OHPs) forms an intersubunit disulphide bond with residue C127′. Such modification induces the expression of a peroxidase that reduces OHPs to their less toxic alcohols. Here, we describe the structures of reduced and OHP-oxidized OhrR, visualizing the structural mechanism of OHP induction. Reduced OhrR takes a canonical MarR family fold with C22 and C127′ separated by 15.5 Å. OHP oxidation results in the disruption of the Y36′-C22-Y47′ interaction network and dissection of helix α5, which then allows the 135° rotation and 8.2 Å translation of C127′, formation of the C22-C127′ disulphide bond, and α6-α6′ helix-swapped reconfiguration of the dimer interface. These changes result in the 28° rigid body rotations of each winged helix-turn-helix motif and DNA dissociation. Similar effector-induced rigid body rotations are expected for most MarR family members. © 2007 Elsevier Inc. All rights reserved.